Anti-terrorism questionnaire development and effectiveness of anti-terrorism education programme on Malaysian public readiness reaction and willingness - Hamzah, Mohd Shaharudin Shah Che (2018)
Terrorism nowadays has become common in many parts of the world and it is slowly coming to Malaysia. Recent developments have seen terrorism evolved in its complexity with the age of information and technology. It now threatens the well-being of innocent life and civil society. This study was initiated by developing and validating a questionnaire, namely TeRRW to access the level of readiness, reaction and willingness among the Malaysia public towards antiterrorism. The internal consistency reliability based on the value of Cronbach’s alpha of TeRRW questionnaire was above 0.70 (ranging from 0.730 to 0.883) and this showed that questionnaire is valid to access the public perception towards terrorism. Then followed with the development of an anti-terrorism educational material which was based on local needs. Using these materials, a crosssectional study and community intervention involving 400 residents from Kota Bharu and Gua Musang districts was conducted within a year from January 2017 until December 2017. The TeRRW questionnaire aims to identify and evaluate the status of readiness, reaction and willingness against terrorism in the community. The association of sociodemographic factors with these three domains were also analyzed. Out of 400 respondents, only 250 (62.5%) showed a reaction and 150 (37.5%) did not react and it further showed only race or ethnicity and job category were found to be significantly associated with those results. The community intervention using anti-terrorism educational material analysis showed that these three domains changed significantly after an intervention was conducted. The anti-terrorism educational material developed to educate and expose the public towards antiterrorism among local communities were found to be effective, but the impacts were decreased within time. This study concluded that the community response towards intervention of antiterrorism such as anti-terrorism educational material was positive to educate and expose the public towards antiterrorism but need to be done in a schedule in order to maximize the impact. This kind of program could increase community alertness level towards terrorism in Malaysia.